E-storybook Oriented on the Chocolate Plantation at Doesoen Kakao Glenmore for Fifth Grade Students - Mulyani, Femi; Hutama, Fajar Surya; Finali, Zetti; Fitriyah, Chumi Zahroul (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the use of less varied learning media. This study aims to investigate the process of developing an e-storybook and to evaluate the validity, effectiveness, and practicality of an e-storybook tailored to cocoa plantations in Doesoen Kakao Glenmore. This development research uses the Borg and Gall development model, but its implementation only reaches the eighth stage. The research subjects were fifth-grade students from an elementary school. The data collection instruments used were observation guidelines, interview sheets, student response questionnaire sheets, documentation sheets, and learning outcome test sheets. Data analysis techniques used, product validation, trials, product effectiveness, and product practicality were carried out through manual calculations using statistical formulas. The development of an e-storybook focused on cocoa plantations resulted in a valid, effective, and practical product. The product's validity obtained a score of 85 (very feasible). The product's effectiveness was demonstrated by the results of student learning tests, which yielded a relative effectiveness of 68% (high effectiveness). The product's practicality obtained a score of 80% (practical). Based on the above data, the e-storybook oriented towards cocoa plantations is a valid, effective, and practical tool for implementing learning. Thus, e-storybooks can be used as an innovative learning medium to help students learn independently and improve their learning outcomes. outcomes.